Digital Brand Disruption - How Opinion Leaders Evoke Unexpected Brand Meanings - Daniel Dietrich (Marketing Review St.Gallen, 2018)
Digital brand management demands anticipatory awareness for the origin of brand meanings. As opinion leaders acquire psychological brand ownership to construct self-identities, they inevitable influence a brand's public perception. An exploration of the brands Birkenstock and New Balance demonstrates the disruptive capacity of today's opinion leaders.
Keywords: 650